2016
DOI: 10.1021/acs.organomet.6b00122
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aryl-, Benzoyl-, and Iminobenzoyl-Palladium(II) Complexes Derived from N-Phenyl Formamide. Synthesis of a Homoleptic Ball-Shaped Tetranuclear Palladium Complex

Abstract: The complex [Pd­{C6H4NHCHO-2}­I­( t Bubpy)] (A, t Bubpy = 4,4′-di-tert-butyl-2,2′-bipyridine) reacts with CO or XyNC, affording the benzoyl or iminobenzoyl complexes [Pd­{C­(O)­C6H4­NHCHO-2}­I­( t Bubpy)] (1) or [Pd­{C­(NXy)­C6H4­NHCHO-2}­I­( t Bubpy)] (2), respectively. Dehydroiodination of 2 with Tl­(acac) (acacH = acetylacetone) produced the iminobenzoyl­(amide) complex [Pd­{C,N-C­(NXy)­C6H4­NCHO-2}­( t Bubpy)] (3) from which complex [Pd­{C,N-C­(NXy)­C6H4­NCHO-2}­(CNXy)2] (4) was obtained upon substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…The bend back angles of 140.6(4) Å (C2–C1–S1) and 131.6(4) Å (C1–C2–N1) in H- 1 are substantially decreased to 122.7(3) Å (C2–C1–S1) and 122.0(3) Å (C1–C2–N1), allowing the chelate coordination. The Pd1–N1 bond length of 2.051(3) Å is comparable to Pd-imine bond length recorded in the literature for S 2 N 2 donor sets and distinctively longer than pure Pd amide bonds. In contrast, the Pd1–S1 distance of 2.348(9) Å falls above the range of 2.232–2.336 Å, which is reviewed for dithiolene Pd­(II) complexes . In contrast to the acdt 2– congener [Tp′W­(CO) 2 (C 2 S 2 ) 2 Pd], complex 9 does not show any reversible redox chemistry.…”
Section: Protective Group Removalsupporting
confidence: 68%
“…The bend back angles of 140.6(4) Å (C2–C1–S1) and 131.6(4) Å (C1–C2–N1) in H- 1 are substantially decreased to 122.7(3) Å (C2–C1–S1) and 122.0(3) Å (C1–C2–N1), allowing the chelate coordination. The Pd1–N1 bond length of 2.051(3) Å is comparable to Pd-imine bond length recorded in the literature for S 2 N 2 donor sets and distinctively longer than pure Pd amide bonds. In contrast, the Pd1–S1 distance of 2.348(9) Å falls above the range of 2.232–2.336 Å, which is reviewed for dithiolene Pd­(II) complexes . In contrast to the acdt 2– congener [Tp′W­(CO) 2 (C 2 S 2 ) 2 Pd], complex 9 does not show any reversible redox chemistry.…”
Section: Protective Group Removalsupporting
confidence: 68%
“…The assignment of 6 as a Pd−iminoacyl complex suggested that the silyl group should be in close proximity to the iminoacyl −CH 3 group in the less sterically encumbered E configuration of the imino group. 85,87,88 Irradiation of the −SiMe 2 Et protons in a 1-D NOESY experiment provided an 8% NOE enhancement of the −CH 3 proton signal, confirming that 6 cannot be the nitrilebound silylpalladium cation (the two groups would be trans) and further supporting the structural assignment as (PCy 3 ) 2 Pd-{C(NSiMe 2 Et)Me} + (see Figure S4 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…Key to differentiating between the trans -(MeCN)­(PCy 3 ) 2 PdSiR 3 + and (PCy 3 ) 2 Pd­{C­(NSiR 3 )­Me} + structures was the 1 H, 13 C-HMBC experiment, which showed the methyl carbon correlating to a weak quaternary carbon resonance at 176.6 ppm. This chemical shift is not in the region expected for the cyano carbon of ligated acetonitrile but is in the chemical shift range expected for a palladium-bound iminoacyl carbon atom. The spectroscopic data are thus inconsistent with either a nitrile-ligated silylpalladium cation or a methylpalladium complex, but they are consistent with 6 being a palladium–( N -silyl)­iminoacyl cation.…”
Section: Resultsmentioning
confidence: 88%